Current status of immunotherapy against gastrointestinal cancers and its biomarkers: Perspective for precision immunotherapy. Issue 4 (22nd June 2018) - Hazama, Shoichi; Tamada, Koji; Yamaguchi, Yoshiyuki; Kawakami, Yutaka; Nagano, Hiroaki
Abstract: Immunotherapy has shown encouraging results for some types of tumor. Although enormous efforts have been made toward the development of specific immunotherapeutic strategies against gastrointestinal cancers, such as adoptive T‐cell transfer, peptide vaccines, or dendritic cell vaccines, the efficacy of immunotherapies prior to the introduction of immune checkpoint inhibitors was not substantial. This article reviews immunotherapy for gastrointestinal malignancies, including cell therapy, peptide vaccine, and immune checkpoint inhibitors, and attempts to resolve the immunosuppressive conditions surrounding the tumor microenvironment, and to construct novel combination immunotherapies beyond immune checkpoint inhibitors. Abstract : This study reviews immunotherapy for gastrointestinal malignancies, including cell therapy, peptide vaccine, and immune checkpoint inhibitors, and attempts to resolve the immunosuppressive conditions surrounding the tumor microenvironment, and to construct novel combination immunotherapies beyond immune checkpoint inhibitors.